Identification of an Alternative Glycyrrhizin Metabolite Causing Liquorice-Induced Pseudohyperaldosteronism and the Development of ELISA System to Detect the Predictive Biomarker - Ishiuchi, Kan'ichiro; Morinaga, Osamu; Yoshino, Tetsuhiro; Mitamura, Miaki; Hirasawa, Asuka; Maki, Yasuhito; Tashita, Yuuna; Kondo, Tsubasa; Ogawa, Kakuyou; Lian, Fangyi; Ogawa-Ochiai, Keiko; Minamizawa, Kiyoshi; et al. (Frontiers in Pharmacology, 2021)
Liquorice is usually used as crude drug in traditional Japanese Kampo and medicine and traditional Chinese medicine (TCM). Liquorice-containing glycyrrhizin (GL) can cause pseudohyperaldosteronism as a side effect. Previously, we identified 18β-glycyrrhetyl-3-O-sulfate (3) as a GL metabolite in Eisai hyperbilirubinuria rats (EHBRs) with the dysfunction of multidrug resistance-related protein (Mrp2). We speculated that 3 was associated with the onset of liquorice-induced pseudohyperaldosteronism, because it was mainly detected in serum of patients with suspected to have this condition. However, it is predicted that other metabolites might exist in the urine of EHBRs orally treated with glycyrrhetinic acid (GA). We explored other metabolites in the urine of EHBRs, and investigated the pharmacokinetic profiles of the new metabolite in EHBRs and normal SD rats. We further analyzed the serum concentrations of the new metabolite in the patients of pseudohyperaldosteronism. Finally, we developed the analyzing method of these metabolites as a preventive biomarker for the onset of pseudohyperaldosteronism using an enzyme-linked immunosorbent assay (ELISA). We isolated a new GL metabolite, 18β-glycyrrhetyl-3-O-sulfate-30-O-glucuronide (4). Compound 4 significantly inhibited rat type-2 11β-hydroxysteroid dehydrogenase (11β-HSD2) and was a substrate of both organic anion transporter (OAT) 1 and OAT3. Compound 4 was also detected in the serum of patients with suspected pseudohyperaldosteronism at an approximately 10-fold lower concentrations than 3, and these concentrations were positively correlated. Compound 4 showed a lower serum concentration and weaker inhibitory titre on 11β-HSD2 than 3. We developed an ELISA system using an anti-18β-glycyrrhetyl-3-O-glucuronide (3MGA) monoclonal antibody to measure the serum concentration of 3 to facilitate the measurement of biomarkers to predict the onset of pseudohyperaldosteronism. Although we found 4 as the secondary candidate causative agent, 3 could be the main potent preventive biomarker of liquorice-induced pseudohyperaldosteronism. Compound 3 was detected in serum at a higher concentration than GA and 4, implying that 3 may be a pharmacologically active ingredient mediating not only the development of pseudohyperaldosteronism but anti-inflammatory effects in humans administered GL or other liquorice-containing preparations.